Taṭwīru Wasāili Ta’allumi Fīdiyū Ar-Rusūmu Al-Mutaħarrikatu ‘Alā As-Sabbūrati Al-Baiḍāi Fī Taħsīni Natāiji Ta’allumi Aṭ-Ṭullābi Bimadrasati Aṡ-Ṡānawiyati Al-Ħukūmiyyati Tis’atun Bāntūl Yūkyākārtā - Wahyu Dwi Taryanto; Nurhadi; Desi Rahmania Zulfa; Ibnu Fikri Ghozali (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2022)
Covid 19 pandemic is the background of this research related to the development of whiteboard animation video learning media. All types of community activities, including teaching and learning activities in schools, get affected and must be stopped due to the pandemic hitting this country. This has caused Arabic language learning, carried out face-to-face between teachers and students (offline), now has to be limited to only the internet network (online). Therefore, teachers need help delivering learning materials, providing learning materials which cause the purpose of learning cannot be obtained optimally—likewise, students who begin to decrease their interest and motivation in learning to reduce student academic results. Hence, based on the problems, researchers developed video-based learning media whiteboard animation to increase student interest and motivation in learning and show the decline of their academic results to achieve the Arabic learning goals properly. This research uses the Reseacrh and Development (R&D) research design as the media development process. It continues with a trial process using three cycles to determine the improvement of each current cycle. This study uses a saturated sampling technique by using the entire population as a sample of all class IX B MTsN 09 Bantul Yogyakarta students. Based on the results of data analysis, there is an increase in the overall average score of students from cycles I, II, and III, which are 77,80, and 86, respectively. Thus, who can conclude that the development of whiteboard animation video learning media is effective and practical in improving the academic result of all students of class IX B MTs N 09 Bantul Yogyakarta. Keyword: Learning Result, Learning Media, Whiteboard Animation Videos ملخص البحث المتعلق بتطوير وسائط تعلم الفيديو الرسوم المتحركة على السبورة البيضاء هو خلفية مع المشكلة الرئيسية ، وهي جائحة Covid-19. ومع الوباء الذي يضرب هذا البلد حاليا، فإن له تأثيرا على تجميد جميع أنواع الأنشطة المجتمعية، بما في ذلك أنشطة التعليم والتعلم في المدارس. وقد تسبب ذلك في أن يقتصر تعلم اللغة العربية، الذي يتم في الواقع وجها لوجه بين المعلمين والطلاب (في وضع عدم الاتصال)، على شبكة الإنترنت فقط (عبر الإنترنت). لذلك ، يواجه المعلمون صعوبات في عملية تقديم المواد التعليمية ، بحيث لا يمكن تحقيق أهداف التعلم على النحو الأمثل. وبالمثل ، فإن الطلاب ، الذين يبدأون في تقليل اهتمامهم وتحفيزهم في التعلم لتقليل نتائج تعلم الطلاب. وبعيدا عن هذه المشكلات، طور الباحثون الرسوم المتحركة القائمة على وسائط التعلم القائمة على الفيديو كمحاولة لزيادة اهتمام الطلاب وتحفيزهم على التعلم وتحسين نتائج تعلم الطلاب بحيث يمكن تحقيق أهداف تعلم اللغة العربية بشكل صحيح. يستخدم هذا البحث تصميم أبحاث Research and Development (R & D) كعملية تطوير الوسائط ويستمر في عملية تجريبية باستخدام 3 دورات ، لتحديد تحسين كل دورة موجودة. استخدمت هذه الدراسة تقنية أخذ العينات المشبعة باستخدام جميع السكان كعينة ، وهي طلاب لصفّ التاسعة ب بمدرسة الثانوية الحكومية 9 بانتول يوكياكارتا. استنادا إلى نتائج تحليل البيانات ، يمكن ملاحظة أن هناك زيادة في المتوسط العام لدرجة الطلاب من الدورة الأولى ، وهي 77 ، والدورة الثانية بنسبة 80 ، والدورة الثالثة بنسبة 86. وبالتالي ، يمكن الاستنتاج أن تطوير وسائط تعلم الفيديو بالفيديو للرسوم المتحركة البيضاء فعال وممكن للاستخدام في تحسين نتائج التعلم الطلاب لصفّ التاسعة ب بمدرسة الثانوية الحكومية 9 بانتول يوكياكارتا. الكلمات الرئيسية : مخرجات التعلم, وسائط التعلم، فيديو الرسوم المتحركة على السبورة البيضاء